Back Cover: Indole Synthesis through Sequential Electrophilic N−H and C−H Bond Activation Using Iodine(III) Reactivity (Chem. Eur. J. 13/2016). Issue 13 (18th February 2016) - Fra, Laura; Muñiz, Kilian
Abstract : The round‐robin of indole cyclization : the eight tentacles of an octopus display the key structures involved in a novel sequential synthesis of indoles. Departing from an aniline bearing a tethered acetylene (lower right), subsequent counterclockwise events include the iodine(III)‐promoted initiation, three charged intermediates throughout the cyclization process and the clipping of the sulfonyl tether to liberate the free indole. More information can be found in the Communication by K. Muñiz and L. Fra onpage 4351 ff.